Nutritional Knowledge, Snacking and Nutritional Status among Indonesian Adolescents - Nur Wahdah Rizqi Amaliah; Iriyani Kamarudin; Ratih Wirapuspita Wisnuwardani (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Adolescent nutrition plays an important role in determining long-term health outcomes. However, poor nutritional knowledge and unhealthy snack consumption are often linked to imbalanced body weight among adolescents. This study aimed to analyze the association between nutrition knowledge and snack consumption behavior with nutritional status among PMR (Youth Red Cross) students at SMKN 15 Samarinda. Objective : Analyzing the relationship between nutritional knowledge and snack consumption among Red Cross Youth members at SMKN 15 Samarinda. Research Methods/ Implementation Methods : A cross-sectional quantitative study was conducted among 41 PMR students at SMKN 15 Samarinda. Data were collected using a validated and reliable questionnaire, which consisted of 15 nutrition knowledge items (Cronbach’s Alpha=0.902). Anthropometric data were obtained to determine Body Mass Index-for-Age (BMI/A) based on the Indonesian Ministry of Health Regulation. Statistical analysis included descriptive statistics and the Chi-square test, with a significance level set at p<0.05. Results : The majority of respondents were female (56.1%) and had a normal nutritional status (82.9%), with a mean BMI of 20.5 kg/m2. The bivariate analysis showed a significant association between nutrition knowledge and nutritional status (p=0.042), indicating that students with higher nutrition knowledge tended to have normal BMI-for-age compared to those with lower knowledge levels. In contrast, no significant association was found between snack consumption behavior and nutritional status. Conclusion/Lesson Learned : Nutrition knowledge significantly influences adolescent nutritional status. Strengthening school-based nutrition education and promoting healthy snack selection are essential strategies to improve adolescent health and prevent malnutrition.